Adaptive behaviors in education institutions before and after COVID-19: A systematic literature review - Walugembe, Ahmad; Ntayi, Joseph; Olupot, Charles; Elasu, Joseph (Frontiers in Psychology, 2022)
Background The final third of the year 2019 was marked by the outbreak of the deadly coronavirus (COVID-19) pandemic. This virus paralyzed almost all economic sectors, including governments, forcing educational institutions to close. School closures resulted in significant learning losses and increased inequality in the education sector across the world. Despite these disruptions, however, available evidence reveals that some countries quickly developed adaptive mechanisms of emergency remote learning systems and other alternative methods to recover from learning losses, such as televisions, telephones, Zoom, social media, Google Classrooms, email, and even the post office. These learning recovery programs are instrumental in preparing world economies for future shocks. Various studies are being conducted to assess the impact of this pandemic from different sectors and perspectives. However, systematic literature reviews documenting the adaptive behaviors in educational institutions before and after COVID-19 are either sparse or nonexistent. Additionally, systematic reviews provide a synthesis of the available evidence, indicate directions for further research, and inform decision-making. This systematic literature review focuses on documenting the adaptation strategies and subsequent positive outcomes emerging from the COVID-19 pandemic. Purpose The purpose of this study was to review published articles on adaptive behavior in educational institutions, and, in particular, review the outcomes of adaptive behavior and coping strategies/mechanisms over time. Methodology The study used a systematic literature review approach as a core methodology for defining answerable research questions, searching the literature for the best available evidence, appraising the quality of the evidence, and collecting and aggregating available data for answering the identified questions. The material was collected using the Science Direct and Emerald databases, which are highly regarded as comprehensive and authoritative. Other documents, especially the reports, were collected from the Google Scholar search engine. Search strings used include “COVID-19 adaptive behavior in educational institutions”, “COVID-19 coping strategies in educational institutions”, “COVID-19 adaptation mechanisms in the education sector”, “adaptive work behavior and COVID-19”, “COVID-19 positive outcomes”, “adaptive work behavior in educational institutions”, and “adaptation strategies in educational institutions”. Findings and conclusion Although the outbreak of the COVID-19 pandemic wreaked havoc on many aspects of life, the education sector was hit more than most other enterprises, and most, if not all, educational institutions were closed as all students were sent home. Educational institutions transitioned to remote teaching and learning strategies. Several studies report a number of positive outcomes ranging from personal (individuals) and institutional (organizations) to technology-based. Among the key technology-based positive outcomes frequently reported in the literature are increased innovations and increased digital resilience in educational institutions, among others.